Att vara manlig socialarbetare - En kvalitativ studie om hur manliga socionomstudenter ser på det sociala arbetet och sin roll som manlig socialarbetare - Tufvesson Alm,Emrik; Lacayo,Noah (2025)
In Sweden, there are currently more women than men active in the welfare profession. At the same time, women are also advancing through traditionally male dominated professions to a much greater extent than men that are advancing through traditionally female dominated professions, such as social work. The purpose of this study was to examine if and how male students in social work, during their studies, have changed their views on social work as a profession and what it means to be a male social worker. Furthermore, the study also aimed to highlight the main motives as to why the students chose to study social work. The study was based on a qualitative method of conducting semi-structured interviews with six male social work students. These students were at the end of their studies and were given open-ended questions as a way for them to open up and reflect on their studies. We applied contemporary masculinity theories and Bandura's social learning theory to analyze our results. The study found that the students had different experiences that led them to choose social work as a profession – experiences such as being influenced by family members and past work experiences. Furthermore, the study also found that the students have reflected on what it means to be a male social worker – both in the context of their studies, during their internship, and in other work situations. Finally, the students also reflected on their role as a males in the context of social work. The findings of the study highlighted that the students had different views on how they were perceived as men studying social work, and how they each were critical to societal beliefs about what it means to be a man.
Keywords: men; social work; social work students; social learning theory; masculinity; reflective practice